Does trade openness influence the real effective exchange rate? New evidence from panel time-series - Ernesto R. Gantman; Marcelo P. Dabós (SERIEs - Journal of the Spanish Economic Association, 2018)
Using a dataset of 101 countries over the 1960-2011 period, we examine the relationship between the real effective exchange rate (REER), on the one hand, and trade openness, trade balance, the terms of trade, factor productivity, and exchange rate regime, on the other one. We use new econometric estimators that deal with the problems of potential endogeneity and cross-sectional dependence that are present in the data, while also allowing for cross-country heterogeneity in the parameters of interest. The findings of the study strongly support the hypothesis that an increase in trade openness produces a depreciation of the REER. The other variables considered in the analysis-factor productivity, trade balance, terms of trade, and exchange rate regime-do not have a statistically significant effect that is robust to different sample compositions and alternative statistical estimators.
Keywords: F13; F31; F41; 330; Real exchange rate; Trade openness; Trade balance; Terms of trade; Total factor productivity; Exchange rate regime